2001
DOI: 10.2134/jeq2001.302440x
|View full text |Cite
|
Sign up to set email alerts
|

Bermudagrass Fertilized with Slow‐Release Nitrogen Sources. I. Nitrogen Uptake and Potential Leaching Losses

Abstract: With the objectives of analyzing N recovery and potential N losses in the warm-season hybrid bermudagrass 'Tifgreen' [Cynodon dactylon (L.) Pers. x C. transvaalensis Burtt-Davy], two greenhouse studies were conducted. Plugs were planted in PVC cylinders filled with a modified sandy growing medium. Urea (URE), sulfur-coated urea (SCU), and Hydroform (HYD) (Hydro Agri San Francisco, Redwood City, CA) were broadcast at rates of 100 and 200 kg N ha-1 every 20 and 40 d. The grass was clipped three times every 10 d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 17 publications
(24 reference statements)
5
21
0
1
Order By: Relevance
“…A similar result was found by comparing urea to controlled-release nitrogen sources where as much as 10% of the urea-N leached compared with less than 1.7% for controlled-release fertilizers (Paramasivam and Alva 1997). Small differences between urea and sulfur-coated urea were reported for greenhouse column studies where total leaching was less than 1% of that added (Quiroga-Garza et al 2001). Other studies have also shown that controlledrelease fertilizer sources will decrease the amounts of nitrogen leached compared with soluble sources (Snyder and Cisar 2000;Shuman 2001Shuman , 2003.…”
Section: Introductionsupporting
confidence: 71%
“…A similar result was found by comparing urea to controlled-release nitrogen sources where as much as 10% of the urea-N leached compared with less than 1.7% for controlled-release fertilizers (Paramasivam and Alva 1997). Small differences between urea and sulfur-coated urea were reported for greenhouse column studies where total leaching was less than 1% of that added (Quiroga-Garza et al 2001). Other studies have also shown that controlledrelease fertilizer sources will decrease the amounts of nitrogen leached compared with soluble sources (Snyder and Cisar 2000;Shuman 2001Shuman , 2003.…”
Section: Introductionsupporting
confidence: 71%
“…Rates exceeding 355 kg ha -1 N can result in a reduced rhizome and root production and increased leaf and stem production, which is not desirable due to the increased requirement for cuts of leaves (mowing), raising the production costs (Quiroga-Garza et al, 2001). The cuts also deplete the carbohydrate pool in lawns which is a reserve for stress periods (Qian & Fry, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…However, the amount of available soil N is insufficient to meet the high demands of the lawn, so regular applications of nitrogen fertilizers are needed to increase grass growth (Bowman et al, 2002;Easton & Petrovic, 2004). Therefore, an ideal lawn quality (color, density and texture) requires an intensive fertilization program with high N rates and irrigation (Exner et al, 1991;Quiroga-Garza et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A qualidade ótima de um gramado requer um programa intensivo de adubação nitrogenada com altas doses (EXNER et al 1991;QUIROGA-GARZA et al 2001). …”
Section: Introductionunclassified